Remittances, Natural Resource Rent and Economic Growth in Sub-Saharan Africa - Pamela E. Ofori; Daryna Grechyna (African Governance and Development Institute (AGDI), 2021)
Despite the established link between oil rent fluctuations and remittances received, its plausible joint effect on economic growth in Sub-Saharan Africa (SSA) remains unexplored. To fill this gap, first we determine whether natural resource rent (composed of oil rent, forest rent and natural gas rent) reduces economic growth in SSA. Second, we examine whether positive macroeconomic signals such as remittances mitigate the negative effect of oil rents on economic growth in a sample of 43 SSA countries spanning 1990-2017. We employ the pooled ordinary least squares, fixed-effects and random-effects, and generalized method of moments. The resulting empirical evidence established are; (1) There is a positive impact of forest rent on economic growth whilst oil rent and natural gas rent have a negative impact on economic growth. (2) There is a positive marginal and net effect on economic growth from the interaction between remittances and oil rent. Also, the unconditional effect of remittances on growth is positive. We further perform a threshold analysis to establish a critical ground that could also influence economic growth positively. This threshold is crucial because above these critical mass remittance inflows mitigate the negative incidence of oil rent on economic growth and below the threshold negative oil rent on growth is completely nullified. This is relevant for policy implications because policy makers are provided with actionable levels of remittances which are easily attainable in sampled countries
Keywords: 330; Remittances; Natural resource rent; oil rent; Economic growth; Sub-SaharanAfrica